Pengaruh Konsentrasi Air Cucian Beras terhadap Pertumbuhan Anggrek Dendrobium sp. Pasca Aklimatisasi - Hartanto, Maisabita Farah Amila; Dewi, Endah Rita Sulistya; Rahayu, Praptining (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to investigate how various concentrations of rice-washed water influence the growth of Dendrobium sp. in the post-acclimatization phase. A Completely Randomized Design (CRD) with one factor and four treatments was used: P0 (0% rice-washed water), P1 (30% rice-washed water), P2 (40% rice-washed water), and P3 (50% rice-washed water). The statistical analysis was conducted using a One-Way ANOVA at a 5% level. If significant differences were found, further analysis was performed using Duncan's Multiple Range Test. The results of data analysis revealed that (1) There were no significant differences in plant height and root length of Dendrobium orchids across the treatments during the post-acclimatization phase; (2) Treatments P1 to P3 did not yield optimal results in terms of plant height, as these concentrations were not suitable for supporting the height growth of Dendrobium orchids in the post-acclimatization phase; (3) The P2 concentration resulted in the longest root growth at 2.39 cm, while the shortest root length was observed in the P0 concentration. Thus, although the different concentrations of rice washing water did not produce statistically significant differences, the P2 concentration showed potential for promoting root growth in Dendrobium orchids during the post-acclimatization phase.